Effective removal of heavy metal ions (Pb, Cu, and Cd) from contaminated water by limestone mine wastes - Aya T. Fathy; Mohamed A. Moneim; Ezzat A. Ahmed; Abdalla M. El-Ayaat; Fatma M. Dardir (Scientific Reports)
Abstract Limestone mining waste and its derived CaO were checked as an adsorbents of pb2+, Cu2+, and Cd2+ ions from water solution. The characterization of Limestone and calcined limestone was studied by using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), Scanning Electron Microscope (SEM), and Surface area measurements (BET). The optimum conditions of sorbent dosage, pH, initial concentration, and contact time factors were investigated for pristine limestone and calcined limestone absorbents. The results indicate that the optimum initial concentrations of (Ci) were 1200, 500, and 300 ppm for Pb, Cu, and Cd, respectively, using calcined limestone adsorbent, while using the pristine limestone adsorbent, the corresponding optimum initial concentrations were 700, 110, and 50 ppm. In the ternary system sorption, the results indicated that the selectivity sequence of the studied metals by limestone can be expressed as Pb2+ > Cd2+ > Cu2+, while calcined limestone exhibits a higher selectivity for Pb2+ compared to Cu2+ and Cd2+. Hence, various adsorption isotherm and kinetic models were examined to explore different patterns and behaviors of adsorption. So, the results indicate that calcined limestone has great potential for eliminating cationic heavy metal species from industrial water solutions.